A Laboratory Investigation on a Tailored Skin and Muscle Flap Variant for the Retrosigmoid Approach - Chibbaro, Salvatore; Cebula, Helene; Zaed, Ismail; Gubian, Arthur; Todeschi, Julien; Scibilia, Antonino; Nannavecchia, Beniamino; Scheer, Louise; Bozzi, Maria Teresa; Mahoudeau, Pierre; Coca, Andres; Signorelli, Francesco; Djennaoui, Idir; Debry, Christian; Ganau, Mario (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction An anatomical study was conducted to test a modified C-shaped flap designed for patients undergoing a keyhole approach and/or minicraniotomy for retrosigmoid approach (KRSA).Materials and Methods Ten heads specimens were used. The surgical technique investigated was based on a 4-cm C-shaped skin incision with medial convexity (placed 8 cm laterally to the external occipital protuberance, with the lower edge terminating 1.5 to 2 cm above the mastoid tip), which followed by careful subperiosteal dissection and completed by reflecting and securing the skin flap layer anteriorly and the muscle flaps superiorly and inferiorly by stitches. Anatomical findings, including depth of surgical corridor till to the cerebellopontine cistern (CPC) as well as the sparing of neurovascular structures, were evaluated in every specimen.Results Twenty surgical approaches to CPC were conducted, resulting in a short working distance to the target (32 mm) without any need for a self-retaining retractor. In every specimen, the integrity of occipital muscles and cutaneous nerves was maintained, and a solid multilayer closure was always achieved. These data suggest that landmarks-based design of this C-shaped incision could be helpful in avoiding damages to the soft tissues encountered during KRSA.Conclusion This modified approach provides a wide surgical corridor to access the CPC while ensuring the minimal invasiveness of the standard S-shaped incision. Compared with the latter, it preserves better the integrity of the surrounding soft tissues and appears less likely to cause any iatrogenic injury to occipital muscles and cutaneous nerves.
Keywords: retrosigmoid approach; C-shaped skin incision; muscle flap; functional pain outcome